Association between the nurse work environment and patient experience in Chilean hospitals: A multi‐hospital cross‐sectional study - Simonetti, Marta; Aiken, Linda H.; Lake, Eileen T. (Journal of nursing scholarship, 2023)
International evidence shows that nurses' work environments affect patient outcomes, including their care experiences. In Chile, several factors negatively affect the work environment, but they have not been addressed in prior research. The aim of this study was to measure the quality of the nurse work environment in Chilean hospitals and its association with patient experience. A cross-sectional study of 40 adult general high-complexity hospitals across Chile. Participants included bedside nurses (n = 1632) and patients (n = 2017) in medical or surgical wards, who responded to a survey. The work environment was measured through the Practice Environment Scale of the Nursing Work Index. Hospitals were categorized as having a good or poor work environment. A set of patient experience outcomes were measured through the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey. Adjusted logistic regression models were used to test associations between the environment and patient experiences. For all outcomes, the percentage of patients satisfied was higher in hospitals with good as compared to poor work environments. In good environment hospitals patients had significantly higher odds of being satisfied with communication with nurses (OR 1.46, 95% CI: 1.10-1.94, p = 0.010), with pain control (OR 1.52, 95% CI: 1.14-2.02, p = 0.004), and with nurses' timely responses in helping them to go to the bathroom (OR 2.17, 95% CI: 1.49-3.16, p < 0.0001). Hospitals with good environments outperform hospitals with poor environments in most patient care experience indicators. Efforts to improve nurses' work environment hold promise for improving patient experiences in Chilean hospitals. Hospital administrators and nurse managers should value, especially in the context of financial constraints and understaffing, the implementation of strategies to improve the quality of nurses´ work environments so that they can provide patients with a better care experience.